Interactive Learning Media Based on Google Sites with Wordwall Assistance for Indonesian Language Learning - Ni Putu Ayu Windi Widiantari; Gusti Ayu Putu Sukma Trisna; Ni Putu Kusuma Widiastuti (Universitas Pendidikan Ganesha, 2025)
Indonesian language learning plays a crucial role in developing students' literacy and communication skills. However, many students still struggle to understand some Indonesian language materials, including direct and indirect speech. This study aims to develop interactive learning media using Google Sites and Wordwall and to determine their feasibility, practicality, and effectiveness in improving student learning outcomes. This study employed a research and development (R&D) approach with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The subjects were 23 fifth-grade students... Data collection was conducted through questionnaires and learning outcome tests. The study found that the developed media achieved feasibility and practicality levels of 98.67% and very good qualifications. The results of the one-sample t-test also showed that the developed media was effective in improving student learning outcomes on direct and indirect sentences. The implications of this study indicate that the use of interactive learning media based on Google Sites, supported by Wordwall, can be an effective and practical innovative alternative for teachers to improve students' understanding and learning outcomes of direct and indirect sentences.